Analisis Health Index Transformator Distribusi Inti Amorphous Untuk Penentuan Skala Prioritas Pemeliharaan Menggunakan Metode AHP-TOPSIS - Heryadi, Tedy (Syntax Literate, 2026)
Amorphous core distribution transformers are increasingly adopted in PLN due to their superior magnetic efficiency and lower core losses. However, these transformers also have the risk of damage that can reduce the reliability of electricity distribution. This study aims to determine the parameter weightings for the Health Index (HI), develop an HI model based on the integrated Analytic Hierarchy Process (AHP) and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS), and generate a prioritized maintenance ranking for amorphous transformers. The AHP method was employed to calculate the weights of seven key diagnostic parameters, resulting in weights of physical condition (0.040), oil leakage (0.163), temperature (0.145), grounding (0.159), load imbalance (0.189), load profile (0.140), and noise level (0.164). Subsequently, TOPSIS was applied to rank 22 transformer units, showing that transformer BTDA110 achieved the highest maintenance priority (ranked 22 based on the lowest health index value), followed by GYPA110 and LITA110, whereas PTP110 held the lowest priority (ranked 1). These findings demonstrate that the combined AHP-TOPSIS approach effectively integrates real condition monitoring data into a quantitative decision-making framework, supporting strategic asset management. The practical implication of this study is the development of an adaptive maintenance prioritization scale, which is expected to enhance power delivery reliability, reduce the risk of transformer failure, and optimize operational expenditure for electric utilities.